Origins and evolution of the wicker from Chimbarongo (1762 - 2017) - Castro San Carlos, Amalia Andrea; Lacoste, Pablo; Mujica, Fernando (Universidad Católica del Norte, Instituto de Investigaciones Arqueológicas y Museo, 2020)
We explained the emergence of the typical product Wicker from Chimbarongo, its origin and development. For this, three key moments of its historical evolution are analyzed (1762, 1914 and 1975). Thanks to their adaptative capacity, they ensured the survival of a prehispanic tradition with 400 producers located in that city. For the analysis, unpublished archival documents (18th and 19th centuries), periodicals of the O'Higgins Region, together with the Bulletin of the National Society of Agriculture, the Bulletin of the Society of Industrial Development and Censuses of the Republic between 1813 and 1920 are used as sources, together with the illustrated weeklies Caras y Caretas of Buenos Aires (Argentina, between 1898 and 1941), Zigzag de Santiago (Chile, 1905-1964) and Sucesos of Valparaíso (Chile, 1902-1934).